ANALISIS SIFAT FISIKA ULTISOL TIGA TAHUN SETELAH PEMBERIAN BAHAN ORGANIK SEGAR DI DAERAH TROPIS BASAH SUMBAR - Yulnafatmawita Yulnafatmawita; Rice Agmi Naldo; Azwar Rasyidin (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2012)
Ultisols as a marginal land need to be reclaimed especially the soil aggregate stability (SAS) under wet tropical area. A research about application of 3 types of fresh organic matter (FOM): Gliricidia sepium dan Tithonia diversifolia) aiming to improve SAS was conducted in Ultisol Limau Manis, wet tropical area, West Sumatra. Fresh organic matter was added to soil at 3 different slope (3, 12, dan 25% slope) in early 2008, then the soil was planted by corn for 4 times until the end of 2009. Corn biomass was return to the land as mulch between crop rows every harversting. The land, then, was fallowed for 1 year (in 2010) before the soil was sampled in 2011 for the physical properties analyses. The results showed that soil organic matter (SOM) content, SAS, permeabilitas, and total pore at 0-20 cm soil depth from plots applied with FOM at all classes of slope were still higher than those control plots. From 3 FOM added, plot added with Tithonia diversifolia still showed better soil physical properties (SOM = 8.3%, SAS = 83). It means that FOM application on Ultisol under wet tropical raiforest still gave effect until 3 years after application.Key Words: Ultisol, stabilitas aggregat, bahan organik segar, bahan organik tanah